Assessing changes in frailty status in an elderly population: Analysis of results from the SFGE tool - Edoardo Carnevale; Michele Bisogno; Edoardo Trebbi; Clara Donnoli; Fausto Ciccacci; Fabio Riccardi; Paola Scarcella; Giuseppe Liotta (PLoS ONE, 2025)
This pilot study explores the relationship between frailty and public health in older adults, evaluating the impact of an Individualized Care Plan (ICP) on frailty status over time. The study involved 125 individuals aged 65 and over recruited through the “Roma Tor Vergata” reference site for healthy and active aging. The Short Functional Geriatric Evaluation (SFGE) questionnaire was used to assess participants’ frailty status at T0 (baseline) and T1 (six-month follow-up). The SFGE evaluates multidimensional frailty, covering psychophysical and socioeconomic domains. Older adults are classified according to four frailty levels: robust, pre-frail, frail, and very frail. Participants identified as pre-frail, frail, or very frail at T0 were also administered the “Sunfrail+” test, which further investigates the bio-psycho-social sphere. An ICP based on multidimensional assessments, was developed for each patient: it was shared with their general practitioner, and recommending specialist visits or rehabilitative interventions. 32% of participants experienced a change in frailty class during the six-month study period. 15.2% improved, 16.8% worsened, and 68% showed no change. Improvement is more frequent in pre-frail individuals, while worsening is predominantly found in robust individuals. Analysis reveals a significant correlation between social and psychological dimensions and the improvement/ worsening of frailty status. Participants who showed improvement reported a greater social activity and improved psychological well-being, while those who worsened reported a reduction in social activities and a decline in socioeconomic and psychological conditions. The study shows that the SFGE is a valuable tool for identifying changes in frailty status and that social networks and psychological well-being are significant factors for frailty status in older adults. Interventions aimed at strengthening social networks of older adults may be useful in preventing or delaying the onset of frailty.